SAT0668 Articular involvement in chronic hepatitis c infection – a preliminary ultrasound study. (12th June 2018) - Ionescu, R.A.; Pana, L.M.; Pompilian, V.M.; Voicu, A.; Caraiola, S.; Ramba, D.; Baicus, C.R.; Dan, A.
Abstract : Background: Chronic hepatitis C is a public health issue. Extra-hepatic manifestations of this infection also include articular involvement, that sometimes mimics rheumatoid arthritis. Objectives: Evaluation of potential articular involvement in patients diagnosed with chronic hepatitis C infection and possible correlations with biological abnormalities. Methods: We evaluated 31 patients with chronic hepatitis C infection, using ultrasound (US) examination of both wrists and the second and fifth interphalangeal joints of the fingers. Then, we looked for possible correlations with various laboratory findings. Results: 29% of patients were symptomatic (pain) at the time of the US examination. 10% of our patients had tenosynovitis of the extensor tendons, another 10% had active synovial hypertrophy (Doppler positive), 31.14% had inactive synovial hypertrophy, 20.9% had erosions and in 20% of them the US examination of the above mentioned joints was normal. 61.29% of patients having US abnormalities, where rheumatoid factor positive. All patients with erosions and inactive synovial hypertrophy, 83.3% of those with active synovial hypertrophy and 67% of those with tenosynovitis where cryoglobulins positive. We found low levels of C3 fraction of complement in 92.3 patients with erosions, 83.3 patients with active synovial hypertrophy, 84.2 patients wit inactive synovial hypertrophy and 50% of patients with tenosynovitis. In 85.7% of patients with active synovial hypertrophy, and 53.8% of pastients with erosions, the C-reactive protein (CRP) levels where elevated. No patient was diagnosed as also having rheumatoid arthritis Conclusions: Even in asymptomatic patients with chronic hepatitis C infection, US examination of the wrists and of the second and fifth interphalangeal joins may reveal abnormalities. Certain types of these are probably correlated with the presence of cryoglobulins and possibly associated with CRP levels, C3 levels and rheumatoid factors positivity. Further studies are needed to verify our finding Disclosure of Interest: None declared